Metabolic and Antidiabetic Effects of Rosa damascena Mill. Extract in Animal Models of Diabetes Mellitus: A Systematic Review - Abdul Aziz Bin Haji Abdul Hamid; Maftuchah Rochmanti; Citrawati Dyah Kencono Wungu (Asian Journal of Social and Humanities, 2026)
Diabetes mellitus is a chronic metabolic disorder affecting more than 537 million adults worldwide, with its prevalence in Indonesia projected to reach 16.09% by 2045. Rosa damascena Mill. contains bioactive compounds with antioxidant, anti-inflammatory, and antihyperglycemic properties; however, its antidiabetic potential has not been systematically reviewed. This systematic review aims to evaluate the metabolic and antidiabetic effects of Rosa damascena Mill. extract in animal models of diabetes mellitus. This review followed the PRISMA 2020 guidelines. A comprehensive literature search was conducted in PubMed, ScienceDirect, Web of Science, and ProQuest, identifying 504 records. Six in vivo animal studies met the inclusion criteria. Diabetes was induced using streptozotocin or a high-fructose diet in male Wistar rats. The risk of bias was assessed using the SYRCLE risk-of-bias tool, and reporting quality was evaluated using the ARRIVE Essential 10 guidelines. Findings were synthesised descriptively. Rosa damascena Mill. extract improved glycaemic and metabolic parameters, with a significant reduction in fasting blood glucose at a dose of 1000 mg/kg (p < 0.0001) and a consistent reduction in triglyceride levels (75 ± 9 vs. 217 ± 18 mg/dL). Methanolic extract demonstrated 98% a-glucosidase inhibition compared with 51% for acarbose. Improvements in insulin sensitivity, increased adiponectin levels, and reduced NF-kB expression were also observed, although changes in HbA1c were not statistically significant. Although Rosa damascena demonstrates promising antidiabetic effects, the available evidence remains limited due to the small number of studies (n = 6), methodological heterogeneity, and unclear risk of bias, highlighting the need for further standardised research.